PENGARUH BUDAYA ORGANISASI, PENEMPATAN SDM, DAN MANAJEMEN TALENTA TERHADAP KINERJA ORGANISASI (Studi Kasus Pada Bpjs Kesehatan) - Zubir, Afrizayanti; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to examine the effect of organizational culture, employee placement, and talent management on the performance of BPJS Kesehatan. Research has been done in the head of regional work unit of BPJS Kesehatan. The data was collected by distributing questionnaires to the respondents. Respondents in this study amounted to 85 employees with simple random sampling technique of 541 employees. The analytical method used in this research is multiple linear regression and the data have been processed by using statistical method with SPSS 24.0 for windows. The results showed that of organizational culture, employee placement, and talent management have significant and positive effects on the performance BPJS Kesehatan. Based on this analyse, the performance of BPJS Kesehatan can be maximized by strengthening organizational culture, making employee placement policies appropriately, and applying talent management strategies effectively